IbM KELURAHAN GULUREJO (KAWASAN PENGRAJIN BATIK) UNTUK MENGATASI MASALAH PENCEMARAN LINGKUNGAN AKIBAT LIMBAH CAIR BATIK - Pratiwi, Yuli; Santoso, Gatot; Waluyo, Joko (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2014)
Batik wastewater in the hamlet Mendiro and Sembungan, Village Gulurejo, District LendahKulonProgo Regency is still a problem for batik craftsmen and society. Contamination of well water and river water in the Village Gulurejo due batik effluent, causing adverse health effects and cause a skin disease such asItchingand other skin disorders.The purpose of this IbM program is to increase knowledge about the technology and batik effluent treatment procedures batik so that the quality of effluent discharged to the environment according to the Liquid Waste Quality Batik is valid and does not pollute the environment. To achieve these objectives there should be a batik wastewater treatment equipment that is easy in operation and can be used interchangeably by batik craftsmen. Achieved results or findings is the realization of sewage treatment plants in the form of batik assemblies elektrokoagulan engineering technology with a method that is effective, efficient, easy in operation and requires a power source of120 watts. Wastewater treatment plant that includes batik: batik waste tank capacity of 500 liters; elektrokoagulan tub capacity of 100 liters; 2 bath deposition capacity of 4,000 liters; 3 bath filtration capacity of 6000 liters which includes coral filter media, split and sand & activatedcharcoal.